2000
DOI: 10.2214/ajr.175.3.1750679
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Hepatic CT with a Multirow Detector CT Scanner

Abstract: Rapid-sequence hepatic helical CT allows selection of the optimal time interval for hypervascular tumor detection. A new paradigm for rapid hepatic CT acquisition-namely, hepatic arterial, portal vein inflow, and hepatic venous phases-is recommended to replace hepatic artery dominant and portal venous phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
125
1
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(146 citation statements)
references
References 8 publications
10
125
1
9
Order By: Relevance
“…Those tumors became visible in this phase that either loosed their contrast slower than normal liver parenchyma or washed out rapidly. [4][5][6][7] Contrast agent used in the study was Diatrizoatemeglumine and Diatrizoate sodium 76% both orally and i.v. Water of low density oral contrast material, 1000 to 1500 cc was given 30 min prior to procedure.…”
Section: Triple Phase Cectmentioning
confidence: 99%
See 1 more Smart Citation
“…Those tumors became visible in this phase that either loosed their contrast slower than normal liver parenchyma or washed out rapidly. [4][5][6][7] Contrast agent used in the study was Diatrizoatemeglumine and Diatrizoate sodium 76% both orally and i.v. Water of low density oral contrast material, 1000 to 1500 cc was given 30 min prior to procedure.…”
Section: Triple Phase Cectmentioning
confidence: 99%
“…This technique has helped to elucidate the imaging features of primary and metastatic liver tumors. 4 Triple phase CT is very crucial in distinguishing a benign lesion from malignant to avoid unnecessary invasive procedures especially in benign tumors like hemangioma. 5 Improved detection and characterization can help determine which hepatic tumors may be amenable to aggressive surgical techniques and which indicate palliative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the iodine concentration measurement could be affected by several factors, such as the dose, concentration and injection rate of iodine contrast material [22]. According to the study by Foley et al [23], the liver parenchyma was well infused by the arterial blood dominative supply and no hepatic venous enhancement in the late arterial phase, which starts approximately 30 s after the initiation of the contrast bolus and lasts for about 12 s. Therefore, the HAP acquisition should be within the late arterial phase to ensure adequate arterial infusion to the liver parenchyma. Yamaguchi et al [24] indicated the optimal delay time of peak hepatic HAP as 19-21 s after the trigger threshold under certain contrast medium infusion conditions by pharmacokinetic analysis and clinical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multidetector helical CT may improve detection of hypervascular lesions, due to its ability to provide even greater temporal resolution of image acquisition (33,34). Improvement in gradient strength and parallel processing techniques (29,35) will further speed MR image acquisition as well, decreasing artifacts due to motion.…”
Section: Discussionmentioning
confidence: 99%